2019
DOI: 10.1080/00220388.2019.1650169
|View full text |Cite
|
Sign up to set email alerts
|

What does it Mean to Make a ‘Joint’ Decision? Unpacking Intra-household Decision Making in Agriculture: Implications for Policy and Practice

Abstract: Strategies to empower women in development contexts frequently address their authority to take decisions within their household, including decisions that are taken jointly by couples. Assessing empowerment in joint decision-making has traditionally followed a dichotomous approach: decisions are either joint or not, with the former associated with women's empowerment. This paper contributes to a more nuanced understanding of the empowerment effects of joint decision-making, based on case study data from Uganda.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(78 citation statements)
references
References 22 publications
3
73
2
Order By: Relevance
“…Gender respondent biasbias in opinions about the role and work of household members-is a known risk for household surveys. This is supported by recent research in Uganda which found that women reported joint household decision-making more often than men, who presented themselves more often as the sole decision-makers; and in Western Kenya where women and men gave different responses relating to control and decision-making around the sale of milk (Tavenner et al 2018;Acosta et al 2019). Based on work with focus groups, the authors propose a set of qualitative indicators to assess decision-making for agricultural productivity and food security.…”
mentioning
confidence: 76%
“…Gender respondent biasbias in opinions about the role and work of household members-is a known risk for household surveys. This is supported by recent research in Uganda which found that women reported joint household decision-making more often than men, who presented themselves more often as the sole decision-makers; and in Western Kenya where women and men gave different responses relating to control and decision-making around the sale of milk (Tavenner et al 2018;Acosta et al 2019). Based on work with focus groups, the authors propose a set of qualitative indicators to assess decision-making for agricultural productivity and food security.…”
mentioning
confidence: 76%
“…While the access to small-scale farming machines is limited across all schools, a trend emerged that girls have an aversion to using and learning about these equipment as well. For these reasons, presenting agriculture as a profitable family business built upon joint decision making and fair allocation of labor responsibilities (Acosta et al, 2020) must be better presented in agricultural education. Other elements necessary for career pathway attraction were also identified.…”
Section: Discussionmentioning
confidence: 99%
“…Where possible, we also defined indicators based on agreement by spouses or on averages of their reported amounts. This is to account for gender differences in perception and reporting of decision making in individual surveys and for the greater likelihood of women labelling a decision as joint where men labels it as their individual decision (Acosta et al, 2020;Ambler et al, 2019). We performed impact estimations on these indicators as a robustness check.…”
Section: Data and Indicator Definitionmentioning
confidence: 99%